36.6k views
5 votes
Expand. If necessary, combine like terms. (x+5)(x−5)

User Zelig
by
4.5k points

2 Answers

4 votes

Answer:


x^(2) -25

Explanation:


(x+5)(x-5)


(x*x)(x*-5)(5*x)(5*-5) multiply the insides by their opposites


x^(2)-5x+5x-25 this can also be shown as
x^(2)+5x-5x-25


x^(2) -25 the
5x and
-5x cancle each other out

User Qrow Saki
by
5.5k points
3 votes

Answer:

x²−25

Explanation:

CLT:

Apply the formula (a-b)(a+b) = a^2*b^2. Substitute 'x' for 'a' and y for 'b'.

(x+5)(x−5)

=(x+5)(x+−5)

=(x)(x)+(x)(−5)+(5)(x)+(5)(−5)

=x²−5x+5x−25

=x²−25

Thats a lot of x's

Hope this helps!

If it does please give me a 'thanks'

User Dizzy
by
5.5k points